Facial reconstruction according to aesthetic units - Nunez Castaneda, José (2020)
Context: The facial subunit principle organizes the facial skin into subunits. Facial reconstruction for skin cancer based on aesthetic units consists of replacing the entire subunit when a large part of a subunit has been removed. Aims: To determine the prevalence of facial skin cancer, their location by facial aesthetic units, and the type of facial reconstruction used in each of them. Settings and Design: An observational cross-sectional study was conducted at the Head and Neck Surgery Service of a general hospital between 2017 and 2018. Materials and Methods: A population census was conducted during this period. Statistical Analysis Used: The categorical variables were expressed as frequencies (percentages). Continuous variables were described as the means and standard deviations or medians and interquartile ranges. Results: The most common skin cancer was basal cell skin cancer, followed by epithelial skin cancer and, at last, melanoma. In general, the most frequent localization of these cancers was the nose. Conclusions: In spite of primary closure being the most common form of reconstruction, a considerable number of patients required facial reconstruction based on aesthetic facial units, with satisfying results.